The Influence of Self-Talk on Athletes’ Performance in National Youth Games Competitions - Daud Rofiat Olisola; Jimoh R Olaitan (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
The application of psychological principles of human performance to help people consistently perform in competitive games is an aspect of interest in sport psychology. Self-talk is one of the cognitive factors believed to contribute to athletes’ performance which are lacking in majority of the athletes attitude based on some factors. This study was to assess athletes’ belief in self-talk relative to their performance in competitive games. The study was a survey conducted in North-Central Nigeria. Participants (N=100) were sampled from contingents who represented twenty-two states that participated in the third edition of the National Youth Games (NYG) held in the University of Ilorin, Nigeria. To guide this study, three research questions were raised and one hypothesis was formulated. An instrument; Belief in Self-Talk Questionnaire (BSQ), was used for data collection. Descriptive statistics and t-test were used to analyze the data collected. Results of this study revealed that belief in use of self-talk during competition significantly improved performance of athletes. Participants reported that positive thoughts make them relax enough to perform well on tasks. Finding also showed that belief in negative thoughts mar performance of athletes. Finally, investigation of this study revealed that use of self-talk by individual sport athletes and team sport athletes differ significantly; the former reported more frequent use of self-talk than the latter.